Epistemologi Tasawuf dalam Pemikiran Fiqh Al-Sya‘Rânî - Miftahul Huda (Universitas Islam Negeri Mataram, 2010)
In the study of Islamic law, epistemology constitutes a fundamental aspect of the law upon which the legitimate concept of the law is based. Epistemology becomes the root of debates regarding the truth of legal reasoning among Muslims who often made a truth clam about their own superior episteme. This causes discrepancies amongst them. This dispute was what al-Sya‘rânî found in his time. As a famous jurist, he sought to resolve it and offered a new theory of law. He contends that the arguments underlying the debates about the epistemology of Islamic law flawed. He wants to demonstrate that the arguments do not fit into the tradition of Islamic thought. This study examines al-Sya‘rânî’s thought in the epistemology of Islamic law. It discusses four issues: the valid path to the knowledge about shari’a, kashf as a source of knowledge, the path to the kashf, and the position and relation of reason, tradition and intuition in Islamic law.